Peranan Kader Bina Keluarga Balita dalam Optimalisasi Tumbuh Kembang Fisik Motorik Anak Usia Dini - Setianingrum, Siska; Desmawati, Liliek; Yusuf, Amin (Journal of Nonformal Education and Community Empowerment, 2017)
This study aims to describe the implementation of activities, the role of cadres, the optimization of physical and motor development of early childhood, as well as supporting and inhibiting factors in Bina Keluarga Balita using a qualitative research approach. Research subjects were four cadres, ten toddlers, and one PLKB. Methods of data collection using observation, interviews, and documentation. The validity of the data is evidenced by triangulation of sources and methods. The results obtained that the implementation of activities consists of opening, core, and closing activities. Optimalization of physical and motor development of early childhood is to know the stage of child development, provide the needs of children, weigh each month, keep the child and the environment clean. The role of the cadre includes the role of implementing activities, extensionists, and motivators. Supporting factors include participant participation, and local government support. Factors inhibiting the lack of understanding of cadres with the material, the number of cadres, and the busyness of the participants.